Application of Copper(II) Schiff Base Complex Grafted in the Silica Network as Efficient Nanocatalyst in Oxidation of Alcohols - Eshtiagh-Hosseini, Hossein; Tabari, Taymaz; Eshghi, Hossein (Asian Journal of Chemistry, 2013)
Bis[S-allyl-b-N-(benzylidene)dithiocarbazato]copper(II) complex was grafted into SiO2 matrix. Heterogenized catalyst was characterized by FT-IR, SEM, EDX TEM, N2 absorption and atomic absorption spectroscopy (AAS) and its catalytic performance in the oxidation of alcohols was investigated. The experimental results showed that the prepared heterogeneous nanocatalyst is an efficient and selective catalyst for examined oxidation reaction. Thus, secondary alcohols were oxidized to ketones and primery alcohols converted to aldehydes by hydrogen peroxide in the presence of newly nanocatalyst in mild conditions.